Identification of Bioactive Compounds in Garlic (Allium sativum L.) with Hypocholesterolemic Potential - Qoyimmah, Aprilya Miftachul; Herdyastuti, Nuniek (Jurnal Pijar Mipa, 2025)
Hypercholesterolemia is a major risk factor for cardiovascular disease, the leading cause of death worldwide. Although statins remain the standard treatment, their long-term use is associated with side effects, sparking interest in safer natural alternatives. Garlic (Allium sativum L.) contains bioactive compounds such as organosulfur compounds (e.g., allicin) and flavonoids (e.g., quercetin and kaempferol), which have been shown to have cholesterol-lowering potential. This study aims to identify bioactive compounds in fresh garlic ethanol extract and powder using liquid chromatography-mass spectrometry (LC-MS), and to evaluate their in vitro anticholesterol activity using the Liebermann-Burchard method. The extracts were prepared using 70% ethanol and tested for their ability to lower cholesterol levels. LC-MS analysis revealed 96 compounds in the fresh garlic extract and 110 compounds in the garlic powder extract. Bioactive compounds such as organosulfur compounds and flavonoids were identified among these compounds. Based on their composition percentages, allicin was more abundant in the garlic powder extract, as were flavonoids such as quercetin and kaempferol, particularly in glycosides. In vitro tests showed cholesterol-lowering effects, with EC₅₀ values of 41,349.08 ppm for the fresh extract and 35,462.29 ppm for the powder extract. Garlic powder extract exhibits higher activity. These findings suggest that garlic, particularly powder form, has potential as a natural cholesterol-lowering agent. Further in vivo studies are needed to confirm its efficacy, mechanism of action, and long-term safety.